Pengaruh Sikap Kerja dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai di Kantor Camat Wulanggitang Kabupaten Flores Timur - Vinsensius Ama Muda; Maria Silvana Mariabel Carcia; Maksima Sima Muda (Peneliti.net, 2021)
This study aims to describe the effect of work attitudes on work morale, the influence of work environment on work morale, analyze the influence of work attitudes and work environment on employee morale, either partially or simultaneously. The population in this study were the employees of the Wulanggitang sub-district office, East Flores Regency, totaling 31 people. Because the population is limited, this research was conducted by census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is done through the F test and t test. The results of the descriptive analysis showed that the variables of Employee Work Attitude, Work Environment and Work Spirit were categorized as good. The statistical results of the F test show that simultaneously all the independent variables are independent. significant effect on Employee Morale. The results of the t-test statistics show that partially the variables of Work Attitude and Work Environment have a positive and insignificant effect on Employee Morale. The results of the determination analysis showed that the two independent variables in this study were able to explain the variations in the ups and downs of the Work Spirit of the Wulanggitang Sub-District Office Employees, East Flores Regency by 22.8%.